PEMBERDAYAAN INTERNET SEBAGAI SOLUSI BELAJAR (LEARNING SOLUTIONS) YANG EFEKTIF DAN EFISIEN - Andi Saryoko (Universitas Bina Sarana Informatika, 2012)
With the development of the Information Technology (IT) and the Internet make us not able to let go of all the fields that exist in our lives more so in the field of education. The Internet open sources of information that was difficult to access. Technologically current information plays a major role in our business, changes in the organization of its structure and organization mannajemen. On the other hand, information technology is also a major role in the scientific development and the primary means in an academic institution. Internet technology is present as a multifunctional media. Communication via the Internet can be done interpesonal (eg e-mail and chat) or en masse, which is known one to many communication (eg, mailing lists). Internet is also able to present in real-time audio-visual as in the conventional method with the application teleconference. Broadly speaking, information technology has a role: (a) to replace the role of the human, in that it can perform the task or process automation, (b) strengthening the role of the man, by presenting information to a task and process, (c) act in restrukturissi the human role, in making changes to a collection of tasks and processes. That the presence of the Internet in education dimension is something that is absolute, and it is a necessity. As a requirement, then the presence of the internet is basically very helpful education to develop teaching and learning situations are more conducive and interactive, effective and efficient. Keywords: Internet, Learning effective and efficient